AFCW3 Economic Update, Spring 2019 : Digitizing Agriculture - Evidence from E-Voucher programs in Mali, Chad, Niger, and Guinea - World Bank Group (World Bank, Washington, DC, 2019)
The agricultural sector is a significant contributor to the economies of Guinea, Mali and Niger. In terms of share of GDP, agriculture represents 16 percent, 38 percent, and 40 percent respectively. It is also a primary source of employment for most of the population (68 percent, 57 percent, and 75 percent respectively). Unfortunately, such critical sector is characterized by low yields due to low input use and quality. The International Fertilizer Development Center (IFDC)estimated the average cereal yields to be 1.6 metric tons per hectare in 2014 in Mali, which is above the sub-Saharan average (1 metric ton/ha) but well below potential yields. With a majority of their land area lying in semi-arid and arid zones of the Sahel and the Sahara desert, increasingly frequent crises arising from the Sahel region’s high vulnerability to climate change--characterized by recurrent extreme weather events such as floods and droughts—low productivity has adverse effects on farmers’ incomes and undermines household food security. Hence the main articlein the present volume is devoted to the innovative effort of introducing e-vouchers schemes, supported by digital means, in Guinea, Mali and Niger. The e-voucher program is built around three key components: a digital platform for SMS messages, a reliable database of electronically-registered farmers in selected regions, and a directory of agro-dealers. In so doing, fertilizers (or seeds) distribution becomes transparent, ensures high quality and as it unfolds, fosters private sector participation. Based on pilot practices in the sub-region, four major lessons are learned. First, targeting is a key determinant of scope and success. In general, targeting depends on the main objective of the program: either poverty reduction, which would aim at farmers located at the lowest deciles of the income distribution, or agricultural productivity, which would also aim at those located a few deciles above. A clear decision in this regard should be taken upfront. Second, in rural populations with high levels of illiteracy, digital technologies should be adapted to their needs, with voice messaging working better than SMS messages. Third, effectiveness of these programs relies on the efficiency of public procurement. In many cases, delays in timely providing agricultural input result from bottlenecks at the procurement stage. As AFCW3 governments become strongly involved in upscaling these approaches, it is my hope that this report will provide further insights to help them in their successful implementation.